Effect of short message service reminders in improving optimal antenatal care, skilled birth attendance and postnatal care in low-and middle-income countries: a systematic review and meta-analysis - Tesfahun Hailemariam; Asmamaw Atnafu; Lemma Derseh Gezie; Binyam Tilahun (BMC Medical Informatics and Decision Making)
Abstract Background Digital health has emerged as a promising solution for enhancing health system in the recent years, showing significant potential in improving service outcomes, particularly in low and middle-income countries where accessing essential health service is challenging. This review aimed to determine the effectiveness of short message services on focused antenatal care, skilled birth attendance, and postnatal care improvement in low and middle-income countries. Method Electronic databases such as PubMed, EMBASE, Scopus, Cochrane, and Google and Google Scholar were searched. We extracted data of antenatal care visits, skilled birth attendance, and postnatal care visits from RCTs and quasi-experimental studies. The quality of included studies was examined using JBI risk of bias assessment tools. A measure of the random-effects model was used to estimate the pooled effect size expressed as Relative Risk (RR) with a 95%CI. The certainty of the evidence was assessed using Grade pro software. Results Twenty-six studies were included in this review. The risk of bias assessment was greater than 50% in included studies. In aggregate, mobile short message service reminders had a significant effect on optimal antenatal care (RR = 1.34, 95% CI: 1.12–1.60), skilled birth attendance (RR = 1.18, 95% CI: 1.05–1.33), and postnatal care (RR = 1.51; 95% CI: 1.34–1.71). There was high heterogeneity for ANC with I2 = 96%; (p < 0.001), skilled birth attendance I2 = 92.6% (p = 0.000), and postnatal care I2 = 78.4% (p < = 0.001). Conclusions Short message service yielded a positive effect in improving antenatal care visit, skilled birth attendance, and postnatal care attendance in low-and middle-income countries. Short message service reminder intervention should be promoted as a tool to improve maternal health service utilization in low and middle-income countries.